AWS development essentials : design and build flexible, highly scalable, and cost-effective applications using Amazon Web Services /: design and build flexible, highly scalable, and cost-effective applications using Amazon Web Services. ([2014]) - Kuppusamy, Prabhakaran; Vyas, Uchit
No abstract available